PENGEMBANGAN SISTEM TERINTEGRASI BERBASIS IOT (INTERNET OF THINGS) UNTUK MONITORING DAN KONTROL KUALITAS AIR PADA BUDIDAYA TAMBAK UDANG DARATAN - Sari, Titin Ervina; Satria, Eko; Rajak, Abdul (Journal of Science and Applicative Technology, 2024)
Water quality is very important for the sustainability of a shrimp farm, starting from the quantity and quality of shrimp harvested is very influential on the good quality of the pond water. The water quality in question is parameters such as water turbidity, a lot or clean of dirt in the pool, a pH value that suits your needs and ammonia content in the pond which is usually produced from shrimp manure. This research designed a water quality monitoring and control tool in shrimp ponds that is integrated automatically through an IoT-based system (Internet of Things) using the thingspeak application as a server and telegram bots as controls. Based on the results of tests that have been carried out, the tool has been able to determine the quality of water correctly. The error percentage was 0.01% for turbidity sensors, 0.05% for TDS sensors, 0.01% for pH sensors and 0.12% for ammonia gas sensors. Based on the results of direct data collection on shrimp ponds for 6 hours, the average value of water turbidity was 3.06 NTU, the lowest was 1.07 NTU and the highest was 5.99 NTU, for the average value of TDS content was 170.98 ppm, 150.00 ppm was the lowest and 204.12 ppm was the highest, for the average pH content was 7.80, the lowest was 7.50 and the highest was 8.74, and the average value of ammonia content was 0.004 ppm, 0.0007 ppm is the lowest and 0.0113 is the highest.